Implementación de una conexión wifi esp8266 en el dispositivo desarrollado por la empresa wx medtech para el registro de datos en tiempo real en la plataforma aws (2023)
The present degree work aims to implement a Wi-Fi connection with the ESP8266 in the device developed by the company WX Medtech for the registration of data in real time in the AWS IoT platform, the company's device only stores measurement data of body fluids in its internal memory, With the implementation of this degree work, the data acquired by the device can be collected and subsequently sent to a database hosted on Amazon Web servers (AWS).